METHODS AND MEANS OF TEACHING - Djurabaeva Ziroat Anvarovna (Galaxy International Interdisciplinary Research Journal, 2022)
The article focuses on the purposeful pedagogical process of organizing and stimulating active educational and cognitive activity of students in mastering knowledge, skills and abilities, developing creative abilities and moral ethical views.